Concepts and models about smart urban transport control systems for city resilience. Issue 2 (2020) - Enjalbert, Simon; Ribeiro, Suzana Kahn; Vanderhaegen, Frédéric
Abstract: The work presented in this paper concerns the control and the efficient assessment of transport systems of a city by studying the impact of climate change, energy supply or human behaviour on different modalities of mobility. Concepts from Human Machine Systems and from green, eco, sustainable, and smart cities, aggregated on resilient city concept, should be an inspiration to develop model for urban transport control systems. A state-of-the-art is proposed to discuss about these concepts and try to determine criteria which should be selected in such process. A first framework based on cooperation and learning concepts is then presented and still must be improved.